Antibiotic exposure at the site of infection: principles and assessment of tissue penetration. Issue 7 (3rd July 2019) - Jager, Nynke G. L.; van Hest, Reinier M.; Lipman, Jeffrey; Roberts, Jason A.; Cotta, Menino O.
ABSTRACT: Introduction : Since the majority of bacterial infections occur at sites outside the bloodstream, antibiotic tissue concentrations are of significant relevance to optimize treatment. The aim of this review is to aid the clinician in choosing optimal regimens for the treatment of extravascular infections. Areas covered : We discuss the principles of antibiotic tissue penetration and assess different approaches to obtain data on this subject. Finally, we present tissue penetration data for several relevant groups of antibiotic agents in a number of extravascular sites. Data were obtained from an extensive literature search in PubMed until February 2019. Expert opinion : There is still a long way to go before reliable information about tissue penetration of antibiotics is sufficiently available to serve as a basis for the design of optimal strategies for drug and dose selection. At this moment, there is a lack of robust data on tissue penetration, where both the sampling and measurement techniques as well as the relationship between tissue concentrations and clinical outcome of antibiotic treatment have to be better defined.